SZ_GERICHTE BEK 2023 137 vom 15. Juli 2024 , notwendige/amtliche Verteidigung (zweiter Rechtsgang) - SZ Gerichte (2024)
notwendige/amtliche Verteidigung (zweiter Rechtsgang) | UP/amtliche Verteidigung